-(c-20)=-2

Simple and best practice solution for -(c-20)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(c-20)=-2 equation:


Simplifying
-1(c + -20) = -2

Reorder the terms:
-1(-20 + c) = -2
(-20 * -1 + c * -1) = -2
(20 + -1c) = -2

Solving
20 + -1c = -2

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-20' to each side of the equation.
20 + -20 + -1c = -2 + -20

Combine like terms: 20 + -20 = 0
0 + -1c = -2 + -20
-1c = -2 + -20

Combine like terms: -2 + -20 = -22
-1c = -22

Divide each side by '-1'.
c = 22

Simplifying
c = 22

See similar equations:

| x=6y-2x-9 | | x^4+3x^3+9x^2+27x=0 | | 7x+3-4x+15=6x+20-3x-2 | | x=gy-2x-9 | | U=2(8n+34)+7(n+1) | | 3x+4y+360=0 | | a^2+3a+3=7 | | 2x-(3+x)= | | 4y^2+4y-28=0 | | 5z-4=8z-4z | | 9x+11-6x-2=2x+4+x+5 | | 2x^2-4x+22=0 | | 7c+18=-5c+78 | | 9p^2+2=11 | | 7(3s+4)=154 | | 5y-7=9+4(y-2) | | 27(x^4)+9+x=0 | | 7(3s+4)=158 | | 4(2l+2)=16 | | n*5= | | n*-5= | | 3(a-7)=15 | | x^2+7+12=(p+[1])(p+2) | | 54-n=25 | | 2n+9j=31 | | 6x+3(x+4)=8(x-3) | | U=3(8n+31)+7(n+1) | | 3(5m+2)-(4m+5)= | | B+45= | | 2x+3-7-x=2x-6-x+2 | | -4(x+3)-7=4x+13 | | n*5+8=7 |

Equations solver categories